Nanometer TiO2 Film-Based Solar Thin Film Manufacturing Technology and Performance Research - Hongliang Wu (Advances in Materials Science and Engineering)
TiO2 sols are usually prepared by sol-gel process using butyl titanate as a precursor, and TiO2 thin films are loaded on ceramic substrates by impregnation lifting method. In this work, the effects of precursor concentration and heat treatment on the properties of TiO2 thin films are investigated to achieve better performance. In addition, the crystal structure of TiO2 is examined by XRD characterization. Experimental results show that the TiO2 films calcined at 500°C are anatase-type structure; the hydrophilic property of the films changes less with the increase of precursor concentration. Moreover, the photodegradation property is improved gradually. The adhesion of the films improved after calcination for each layer of TiO2 films loaded on the ceramic sheet.